2023
DOI: 10.3390/jpm13030510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of 2D and 3D Templating for Revision Total Hip Replacement

Abstract: Introduction: Revision hip arthroplasty is a challenging surgical procedure, especially in cases of advanced acetabular bone loss. Accurate preoperative planning can prevent complications such as periprosthetic fractures or aseptic loosening. To date, the accuracy of three-dimensional (3D) versus two-dimensional (2D) templating has been evaluated only in primary hip and knee arthroplasty. Methods: We retrospectively investigated the accuracy of 3D personalized planning of reinforcement cages (Burch Schneider) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…There are different methods of preoperative templating for THRs, acetate sheets on digital radiographs, 2D templating using computer software, and 3D templating which relies on cross-sectional imaging such as CT scans of the pelvis [ 7 , 8 ]. A recent meta-analysis suggested that 3D templating may be more accurate than traditional 2D methods, however the clinical benefits of this increased accuracy are not known [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods of preoperative templating for THRs, acetate sheets on digital radiographs, 2D templating using computer software, and 3D templating which relies on cross-sectional imaging such as CT scans of the pelvis [ 7 , 8 ]. A recent meta-analysis suggested that 3D templating may be more accurate than traditional 2D methods, however the clinical benefits of this increased accuracy are not known [ 9 ].…”
Section: Discussionmentioning
confidence: 99%